The secret history: a key fandom of the Dark Academia - López Millán, Lara (2022)
This article approaches the Dark Academy aesthetic community, which became popular during the pandemic, and explores its relationship with the fandom of the novel The Secret History (Donna Tartt, 1992). To carry out the analysis, we study the practices exercised by the members of Dark Academy on Tumblr, selected due to its multiple content circulation possibilities and community-creating tools, and the results of an online survey of 1000 members of the aesthetic community. As a result, we highlight how the fandom of Donna Tartt's work is key to the development and evolution of this new community.